Prediction of interaction of citric acid modified cellulose with water region using molecular modelling technique - Wan Mohamed Daid, Wan Nor Asyikin (2018)
The discharge of toxic heavy metals in water bodies is a serious pollution problem affecting water quality, creating a direct hazard to human health if present in drinking water. In this study, metal of interest was ferric ion (Fe³+) due to potential pollution impact on the aquatic environment. Ferrous ion (Fe²+) which are dissolved in water will be converted into complexes ferric ion by bacteria activities and can be removed by citric acid modified cellulose (CAMC). The purpose of this research is to improve the method to remove heavy metal from a polluted water as the cellulose in nano-crystalline forms are less exploited for adsorption application. In this findings, chemically modified cellulose was used instead of cellulose because it has higher adsorption capacities, great chemical strength and good resistance to heat. As part of Phyto-Adsorption Remediation Method, CAMC was used to treat ferric ion. However, there is a large possibility that CAMC molecule might interact with water molecule that contain hydrogen and oxygen bond and hence pose as a competitor to ferric acid and reduces the efficiency of CAMC in ferric ion removal. Thus, the aim of this work is to identify the most stable hydrogen bond between CAMC and water, by using a computational technique. The interaction between the water molecules and CAMC was observed by varying the volume of water molecule with modified cellulose by an expansion in amorphous region. The simulation result showed that for water loading less than 20 molecules, the interaction between water molecules and CAMC is higher at temperature 311K, whilst for water loading higher than 20 molecules, the interaction weakens at higher temperature. This work proved that water molecules have the tendency to bind to hydroxyl group of glucose ring, to oxygen of ester and to oxygen of anhydride acid of the CAMC molecule. The calculation of coordination number has shown that the number of atoms present in the first hydration shell (of radius < 2.5Å) is more as the temperature increases from 298K to 311K. Whilst, at radius >2.5Å, cell temperature is not significant to the number of atoms present.